Relation Between Awe and Environmentalism: The Role of Social Dominance Orientation - Zhao, Huanhuan; Zhang, Heyun; Xu, Yan; Lu, Jiamei; He, Wen (Frontiers in Psychology, 2018)
The present study attempts to explore the effect of awe on environmentalism and the mediating role of social dominance orientation in generating this effect. In Study 1, a series of questionnaires were used to investigate the correlation among trait awe, social dominance orientation, and ecological behavior. Results demonstrated that, while trait awe was positively correlated with ecological behavior, it was partially mediated by social dominance orientation. In follow-up studies, two priming experiments were conducted to test the causal relationship and the psychological mechanisms between awe and environmentalism. Results revealed that inductions of awe (relative to various control states) decreased participants’ social dominance orientation, which in turn partially enhanced their willingness to make personal sacrifices for the environment (Study 2), and intentions to engage in pro-environmental behavior (Study 3). This study not only corroborates the critical role of awe in promoting environmentalism, but also highlights the importance of social dominance orientation in explaining why awe increases environmentalism. Implications and future directions were also discussed.